A simultaneous quantitative determination of both natural and synthetic cannabinoids in bio-matrix by ultra-high pressure liquid chromatography tandem mass spectrometry - Cromarty, Allan Duncan (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.